Unveiling the Armed Forces Special Powers Act - Jha, Minu (2016)
The Armed Forces Special Powers Act (AFSPA), 1958, has consistently remained a contentious issue earning epithets such as 'draconian' and 'black law' over the years. The North-Eastern state of Manipur, in fact, became the first testing ground for the AFSPA and has remained imposed for decades. Use or rather misuse of repressive laws like these by any democracy needs serious contemplation. The article in the stated background looks at the AFSPA through the established democratic notions of upholding the supremacy of the judiciary and primacy of the rule of law. In doing so, it discusses in detail the various provisions of the Act and the human rights abuses. In the latter half, it unfolds the role of civil society, political parties and the judiciary in affirming their demand for the review or repeal of the Act. - Reproduced.
Keywords: Armed Forces Special Powers Act; Armed Forces